THE LIVED EXPERIENCE OF SMOKERS WORKING IN SMOKING REGULATED ENVIRONMENTS - Konen, Sherry L. (My University, 2010)
Smoking and secondhand smoke are harmful to health. As information about the negative affects has increased, so have regulations. Regulations are growing with the workplace becoming a primary target. The workplace is a particularly sensitive environment, potentially affecting the smoker's job security if the regulations are not adhered to. Sentinel studies, such as COMMIT and ASSIST, focused on the effect of policies and regulations on smoking reduction. They provided beneficial evidence in the light to moderate smoker, but failed to show benefits in the heavier smoker. The purpose of this study was to examine the experience of heavy smokers working in smoking regulated environments in order to understand their challenges and discover their adaptive mechanisms. This information can then be applied to the development of effective interventions. The theoretical framework for the study was Roy's Adaptation Model. It was applied with the nursing process to analyze behavior and evaluate the effectiveness of smoking regulations on the person's adaptability. A qualitative descriptive phenomenological method was utilized to gain information about the smokers' experiences. Regulated smokers were chosen through a nonrandomized, purposive sample method involving three types of worksites including: factory, medical facility, and restaurant. Ten individuals, 18 years of age or older, who smoked, on average, a minimum of 10 cigarettes a day, and worked at least 8 hours per day in a smoking regulated environment were included in the study. An open-ended survey was conducted with voluntary participants. Measures were taken to ensure participant confidentiality and protection. The data was analyzed using Giorgi's method. Presenting themes served as the basis for future development of Nurse Practitioner interventions.
A Clinical Paper Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Family Nurse Practitioner
Keywords: Passive smoking; Tobacco use; Smoking